Integrating Early Transcriptomic Responses to Rhizotoxins in Rice (Oryza sativa. L.) Reveals Key Regulators and a Potential Early Biomarker of Cadmium Toxicity - Huang, Li-Yao; Lin, Chung-Wen; Lee, Ruey-Hua; Chiang, Chih-Yun; Wang, Yung-Chuan; Chang, Ching-Han; Huang, Hao-Jen (Frontiers in Plant Science, 2017)
As sessile organisms, plants were constantly challenged with biotic and abiotic stresses. Transcriptional activation of stress-responsive genes is a crucial part of the plant adaptation to environmental changes. Here, early response of rice root to eight rhizotoxic stressors: arsenate, copper, cadmium, mercury, chromate, vanadate, ferulic acid and juglone, was analyzed using published microarray data. There were 539 general stress response (GSR) genes up-regulated under all 8 treatments, including genes related to carbohydrate metabolism, phytohormone balance, and cell wall structure. Genes related to transcriptional coactivation showed higher Ka/Ks ratio compared to the other GSR genes. Network analysis discovered complicated interaction within GSR genes and the most connected signaling hubs were WRKY53, WRKY71 and MAPK5. Promoter analysis discovers enriched SCGCGCS cis-element in GSR genes. Moreover, GSR genes tend to be intronless and genes with shorter total intron length were induced in a higher level. Among genes uniquely up-regulated by a single stress, a phosphoenolpyruvate carboxylase kinase (PPCK) was identified as a candidate biomarker for detecting cadmium contamination. Our findings provide insights into the transcriptome dynamics of molecular response of rice to different rhizotoxic stress and also demonstrate potential use of comparative transcriptome analysis in identifying a novel potential early biomarker.